Biaxial bending design of solid steel storage rack uprights in global buckling. (September 2022) - Talebian, Nima; Gilbert, Benoit P.; Miller, Dane; Karampour, Hassan
Abstract: This study aims at investigating the biaxial bending capacity of cold-formed steel (CFS) storage rack uprights undergoing global (lateral-torsional) buckling. A previously published and validated biaxial bending numerical model for local and distortional buckling of CFS rack uprights is initially validated in this paper for global buckling and then used to evaluate and analyse the biaxial bending response of nine unperforated upright cross-sections. Nine biaxial bending configurations were considered per cross-section. Results show that a nonlinear interactive relationship typically governs the biaxial bending of the studied uprights. This relationship is discussed and analysed for different cross-sectional slenderness. The numerical capacities are compared with both the classical DSM predictions and the use of inelastic reserve capacity in the DSM. Results show that the classical DSM equations underestimate the biaxial bending capacity by up to 55% but results in better predictions when the inelastic reserve capacity is considered. Finally, an extended range of inelastic reserve strength for global buckling is proposed which results in a 14% improvement of the DSM predictions. The appropriate form of the DSM to estimate the global biaxial bending capacity of unperforated cold-formed steel storage rack uprights is discussed. Highlights: Validated Finite Element (FE) model to predict global biaxial bending response of storage rack upright sections Evaluation of currently available DSM equations to predict global biaxial bending capacity of storage rack upright sections Newly proposed extended range of inelastic reserve strength for global buckling